Effect of maternal body mass index on maternal and fetal outcome in Maternity Teaching Hospital in Sulaimani - Fars, Gona Othman; Ismail, Nian Hakim; Abdulkarim, Awayi Xazy (Sulaimani Journal for Pure and Applied Sciences, 2016)
The current study was undertaken to evaluate the effect of body mass index on birth outcome. This study was carried out for the period of 20 th February to 18 th April of 2014, sample of (50) pregnant women who have been attended maternity teaching hospital in Sulaimani city, to determine the effect of body mass index on birth outcome, and to explore association between some socio-demographic and obstetrics characteristics with outcome of birth. The result shows that there is no significant association between body mass index and outcome of labor or delivery.
Keywords: BMI; Birth outcome; Baby outcome